2020
DOI: 10.3329/bmrcb.v46i1.47463
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine level in children with Juvenile Idiopathic Arthritis

Abstract: Background: Juvenile Idiopathic Arthritis (JIA) is the most common chronic rheumatic disease of childhood and a leading cause of short and long-term disability. Abnormal level of serum homocysteine (Hcy) may be found in Juvenile idiopathic arthritis (JIA) patients. Some studies were done on serum homocyestine levels in children with JIA which showed conflicting results. So far, no study regarding the Hcy level in JIA patients was done in Bangladesh. Objectives: The study was aimed to assess the homocyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some combination therapies display little difference compared with monotherapy; for example, methotrexate plus sulfasalazine does not produce a significant change in disease activity compared with methotrexate monotherapy 18. Notably, combination therapy of methotrexate plus cyclosporine was measured using the outcome measure of choice for clinical trials of drugs used to treat RA.…”
Section: Discussionmentioning
confidence: 99%
“…Some combination therapies display little difference compared with monotherapy; for example, methotrexate plus sulfasalazine does not produce a significant change in disease activity compared with methotrexate monotherapy 18. Notably, combination therapy of methotrexate plus cyclosporine was measured using the outcome measure of choice for clinical trials of drugs used to treat RA.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses reveal that folic acid supplementation can reduce hepatotoxicity and the frequency of GI side-effects associated with MTX, lower transaminases levels and limit the number of patients choosing to discontinue MTX [16]. In parallel, the low folic acid levels associated with MTX treatment are also responsible for the elevated circulating concentrations of homocysteine (HCY) observed among patients with RMDs (including JIA) on MTX, compared to those on anti-tumor necrosis factor-α (anti-TNF-α) treatment [16][17][18][19][20]. HCY reduces the activity of the asymmetric dimethylarginine (ADMA) decomposing enzyme and carotid intima-media thickness, initiating atheromatosis and atherosclerosis, while multiplying the cardiovascular disease (CVD) risk of patients, irrespective of the methylenetetrahydrofolate reductase (MTHFR) C677T genotype [17,21].…”
Section: Medication-induced Nutrition-related Side Effects 211 Mtx Ad...mentioning
confidence: 99%
“… 16 Most studies worldwide have not reported on the appropriateness of antibiotic or antiparasitic use in children under 5 with AD. 19 - 22 A systematic review on harmful practices in the management of childhood diarrhea in low- and middle-income countries revealed a wide range of antibiotic use prevalence, varying from 10% to 77%, suggesting that high rates of antibiotic use may be inappropriate. 23 The review also emphasized the variability in accuracy when analyzing antibiotic use, particularly when relying on questionnaires administered to physicians or caregivers, which often yield highly inaccurate findings.…”
Section: Introductionmentioning
confidence: 99%